MIR210HG Accelerates the Progression of Colorectal Cancer and Affects the Function of Colorectal Cancer Cells by Downregulating miR-1226-3p - Jiang, Chunyan; Zhao, Xiaofeng (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Colorectal cancer (CRC) is a widespread cancerous disease with an unfavorable prognosis. MIR210HG appears to have a significant connection with the development of CRC, but the precise regulatory mechanism remains obscure. Materials and Methods: Quantitative real-time polymerase chain reaction was utilized to determine expression quantities of MIR210HG and miR-1226-3p. The proliferative capacity of CRC cells was measured by cell counting kit-8. The apoptosis rate of cells was examined using flow cytometry. The invasive capability was assessed through the transwell experiment. The targeted regulation of MIR210HG and miR-1226-3p was validated through dual-luciferase reporter gene experiments. Results: In carcinoma tissues and blood serum of colorectal cancer patients and cell lines, MIR210HG expression was upregulated, while the miR-1226-3p expression was downregulated. MIR210HG had a diagnostic and prognostic value for CRC patients. MIR210HG may target and regulate miR-1226-3p. MIR210HG may have the capacity to augment the vitality and invasion of CRC cells and suppress cell apoptosis, and this influence is counteracted by miR-1226-3p. Conclusion: lncRNA MIR210HG accelerated the progression of colorectal cancer by controlling miR-1226-3p. lncRNA MIR210HG/miR1226-3p may potentially serve as therapeutic targets for addressing colorectal cancer. Cite this article as: Jiang C, Zhao X. MIR210HG accelerates the progression of colorectal cancer and affects the function of colorectal cancer cells by downregulating miR-1226-3p. Turk J Gastroenterol. 2024;35(12):889-899.